A grand design : the art of the Victoria and Albert Museum - 4 0 16; Victoria and Albert Museum; Baker, Malcolm,;Richardson, Brenda,;Burton, Anthony; 5 Baltimore Museum of Art. (New York :;Baltimore : Harry N. Abrams,;Baltimore Museum of Art, 1997)
Photographs and text help describe over 250 different artifacts that are exhibited in London's Victoria and Albert Museum.
Catalog of a traveling exhibition shown at the Baltimore Museum of Art, and other museums Oct. 1997-Jan. 2000.
Includes bibliographical references (p. 401-411) and index.
Library Journal Starred;Reference and Research Book News
Adult;Adult.
Keywords: 2 -- 0; Exhibitions.;Exhibitions. -- Victoria and Albert Museum;Victoria and Albert Museum.;Victoria and Albert Museum;Victoria and Albert Museum. -- 6; Art;Art;Art -- England;London -- Exhibitions.;Exhibitions.;Exhibitions.; 20; 2